2016
DOI: 10.1016/j.elstat.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the impact of conductor surface type on wet weather HVDC corona characteristics

Abstract: Corona behavior of HVDC overhead lines plays a significant role when dimensioning transmission lines. Rain constitutes an important study case since corona effects (e.g. losses, discharge amplitudes) are considerably affected. In this paper, imaging methods are introduced to investigate the impact of rain on corona behavior. Geometrical properties of rain drops on a stranded conductor were extracted. UV-images were used to precisely locate discharges. The methods' capabilities are demonstrated using data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 25 publications
(26 reference statements)
3
25
0
Order By: Relevance
“…In reality, however, during steady rain, corona originates nearly exclusively from suspended drops on the lower side of the conductor [38], similar to the 'v v' case. Also, the area with the strongest Poisson field enhancement ('inwards') does not coincide with the area with a low E on ('downwards').…”
Section: Discussion Of Bipolar Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In reality, however, during steady rain, corona originates nearly exclusively from suspended drops on the lower side of the conductor [38], similar to the 'v v' case. Also, the area with the strongest Poisson field enhancement ('inwards') does not coincide with the area with a low E on ('downwards').…”
Section: Discussion Of Bipolar Resultsmentioning
confidence: 99%
“…However, certain phenomena that occur with real raindrops are not represented by the metallic disturbances. The shape of raindrops, for example, varies with the applied electrical field and a critical drop size and field is necessary to form Taylor cones [38]. Furthermore, drops behave dynamically and eject water while producing corona.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most of the existing data was derived from outdoor experiments with typically highly fluctuating rain intensities. However, previous studies have shown that the corona performance will indeed not be constant, but vary over time during transient rain periods [4], [13], [14]. A very important factor for this is the deformation of the water drops in an electric field, with different corona source geometries causing very different corona characteristics [4], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…With an application of a sufficiently high electric field, the water drops will form a spike-shaped Taylor cone with a very high electric field at the tip [17], typically causing lower audible noise due to high frequent hissing corona with a high repetition rate, loss current and space charge density, but low amplitude [4], [16]. Therefore, the reason for the decrease of audible noise in rain for HVDC is generally attributed to the shielding effect of these space charges [13], [18], while the DC corona current increases with rain intensity [19].…”
Section: Introductionmentioning
confidence: 99%